2018
DOI: 10.14419/ijet.v7i4.11.20785
|View full text |Cite
|
Sign up to set email alerts
|

Animation Effectiveness for E-Learning with Progressive Web App Approach: a Narrative Review

Abstract: Understanding the content of a subject is the most fundamental thing a student should do to acquire the skills and knowledge. Animation is one way to provide an interesting way of learning. ALETRIA project is the reason to support the students for use animation methods that developed in novel e-learning concept. As a first step, the study of animation and e-learning development became the basis of this narrative literature. Terms of search that used in this paper is animation for learning, engagement and learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…(Teacher 5) Some of them also mentioned that they used various methods to reach to their students including giving worksheet through WhatsApp, and sending pictures or videos as extra support materials. For example, a combination of audio, visual and animation effects made e-learning more appealing and effective (Wijaya & Helmi, 2018). Their choices of methods were strongly related to students' home area which had poor internet connection.…”
Section: Teaching Methods For Effective Lessonmentioning
confidence: 99%
See 1 more Smart Citation
“…(Teacher 5) Some of them also mentioned that they used various methods to reach to their students including giving worksheet through WhatsApp, and sending pictures or videos as extra support materials. For example, a combination of audio, visual and animation effects made e-learning more appealing and effective (Wijaya & Helmi, 2018). Their choices of methods were strongly related to students' home area which had poor internet connection.…”
Section: Teaching Methods For Effective Lessonmentioning
confidence: 99%
“…The rapid developments and innovations in technology provided opportunities and new features in language learning. For example, a combination of audio, visual and animation effects made the e-learning more appealing and effective (Wijaya & Helmi, 2018). Moreover, e-learning is also considered a cost-efficient and timesaving tool in learning a language.…”
Section: E-learning In Esl Classroommentioning
confidence: 99%
“…Rapidly developments in technology provide learners with new opportunities to explore language learning. For instance, the combination of audio, visual, and animation effects has made online learning more appealing and effective (Wijaya & Helmi, 2018). This is evident in the use of online learning tools, such as Kahoot, Quizizz, Quizlet, and Plickers, which add the element of fun and meaningful learning to the learning process.…”
Section: B Online Esl Learningmentioning
confidence: 99%
“…To gain the attention from the learners, Adam et al (2017) suggested that using animations can enrich learners' interests and simplify the complex content. Wijaya and Abbas (2018) asserted that traditional media, static slides, may not fully present complicated subject matter and concepts. The use of animation aids to have a more accurate portrayal of these difficult ideas because it displays stages on a regular basis.…”
Section: Introductionmentioning
confidence: 99%